Genomic study of nonsyndromic hearing loss in unaffected individuals: Frequency of pathogenic and likely pathogenic variants in a Brazilian cohort of 2,097 genomes - Quaio, Caio Robledo D’ Angioli Costa; Coelho, Antonio Victor Campos; Moura, Livia Maria Silva; Guedes, Rafael Lucas Muniz; Chen, Kelin; Ceroni, Jose Ricardo Magliocco; Minillo, Renata Moldenhauer; Caraciolo, Marcel Pinheiro; Reis, Rodrigo de Souza; Azevedo, Bruna Mascaro Cordeiro de; Nobrega, Maria Soares; Teixeira, Anne Caroline Barbosa; et al. (Frontiers in Genetics, 2022)
Hearing loss (HL) is a common sensory deficit in humans and represents an important clinical and social burden. We studied whole-genome sequencing data of a cohort of 2097 individuals from the Brazilian Rare Genomes Project who were unaffected by hearing loss to investigate pathogenic and likely pathogenic variants associated with nonsyndromic hearing loss (NSHL). We found relevant frequencies of individuals harboring these alterations: 222 heterozygotes (10.59%) for sequence variants, 54 heterozygotes (2.58%) for copy-number variants (CNV) and four homozygotes (0.19%) for sequence variants. The top five most frequent genes and their corresponding combined allelic frequencies (AF) were: GJB2 (AF = 1.57%), STRC (AF = 1%), OTOA (AF = 0.69%), TMPRSS3 (AF = 0.41%), OTOF (AF = 0.29%). The most frequent sequence variant was GJB2:c.35del (AF = 0.72%), followed by OTOA:p.(Glu787Ter) (AF = 0.61%), while the most recurrent CNV was a microdeletion of 57.9 kb involving the STRC gene (AF = 0.91%). An important fraction of these individuals (n=104; 4,96%) presented variants associated with autosomal dominant forms of NSHL, which may imply the development of some hearing impairment in the future. Using data from the heterozygous individuals for recessive forms and the Hardy–Weinberg equation, we estimated the population frequency of affected individuals with autosomal recessive NSHL to be 1:2,222. Considering that the overall prevalence of HL in adults ranges from 4% to 15% worldwide, our data indicate that an important fraction of this condition may be associated with monogenic origin and dominant inheritance.